Answer and explanation:
The expression P-2P+3P-4P cannot have the same values for different values of P. Let us illustrate this by substituting different values of P in the expression:
If P= 2
Substitute P=2 in the expression
2-2×2+3×2-4×2
=2-4+6-8
=-4
If P= 3
Substitute P=3 in the expression
3-2×3+3×3-4×3
=3-6+9-12
=-6
If P = 1
Substitute P=1 in the expression
1-2×1+3×1-4×1
= 1-2+3-4
= -2
If P = -2
Substitute P=1 in the expression
-2-2×-2+3×-2-4×-2
= -2+4-6+8
=4
Therefore we can see from the above that the expression has different values for different values of P